1996
DOI: 10.1136/bmj.313.7051.195
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and the sudden infant death syndrome: results from 1993-5 case-control study for confidential inquiry into stillbirths and deaths in infancy

Abstract: This study confirms the increased risk of the sudden infant death syndrome associated with maternal smoking during pregnancy and shows evidence that household exposure to tobacco smoke has an independent additive effect. Parental drug misuse has an additional small but significant effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
205
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(211 citation statements)
references
References 16 publications
3
205
1
2
Order By: Relevance
“…Bed sharing should be avoided, regardless of the infant's age, if the mother is a smoker, has taken drugs or alcohol, or if the baby sleeps in a place other than the crib, usually a sofa 8, 12, 13, 14.…”
Section: Discussionmentioning
confidence: 99%
“…Bed sharing should be avoided, regardless of the infant's age, if the mother is a smoker, has taken drugs or alcohol, or if the baby sleeps in a place other than the crib, usually a sofa 8, 12, 13, 14.…”
Section: Discussionmentioning
confidence: 99%
“…Death rates from SIDS are higher among African-American infants, 26 and with tobacco exposure, 26,27 and perhaps with bedsharing. 25 Although we identified more risk factors for SIDS in the CY group, this vulnerable group less often received instruction for the recommended sleep positions.…”
Section: Discussionmentioning
confidence: 99%
“…17 In addition to the prone position, several studies have reported the association of SIDS with infant hyperthermia, 18 -23 swaddling, 23 and suffocation. 23,24 Bedsharing 25 and exposure to tobacco smoke 26,27 have also been reported to increase the risk for SIDS. Our study was undertaken primarily to determine the sleep positioning instructions given by hospital personnel in our community and the actual positions practiced by parents.…”
mentioning
confidence: 99%
“…We create a dummy variable that indicates if the mother smoked after the fourth month of pregnancy. Smoking during pregnancy has been found to be related with cognitive deficiencies and other health problems in the medical and epidemiological literature (see for instance Blair et al, 1996;Conter et al, 1995;Naeye and Peters, 1984;Williams et al, 1998). Furthermore, we observe the mother's age at birth.…”
Section: Background Variablesmentioning
confidence: 56%